New porous material to enhance the kinetics of clathrate process: application to precombustion carbon dioxide capture - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Environmental Science & Technology, 2013)
In this work, the performance of a new porous medium, polyurethane (PU) foam in a fixed bed reactor for carbon dioxide separation from fuel gas mixture using the hydrate based gas separation process is evaluated. The kinetics of hydrate formation in the presence of 2.5 mol % propane as thermodynamic promoter was investigated at 4.5, 5.5, and 6.0 MPa and 274.2 K. Significantly higher gas consumption and water conversion to hydrate was achieved when PU foam was employed. PU foam as a porous medium can help convert 54% of water to hydrate in two hours of hydrate formation. In addition the induction times were very low (<3.67 min at 6.0 MPa). A normalized rate of hydrate formation of 64.48 (+/- 3.82) mol.min(-1).m(-3) was obtained at 6.0 MPa and 274.2 K. Based on a morphological study, the mechanism of hydrate formation from water dispersed in interstitial pore space of the porous medium is presented. Finally, we propose a four step operation of the hydrate based gas separation process to scale up.